The girl with a clock for a heart : a novel - Swanson, Peter, 1968- (William Morrow, an imprint of HarperCollinsPublishers, 2014)
When Liana Dector, a woman who is possibly a cold-blooded killer wanted by the police, storms into his favorite Boston tavern demanding his help, George Foss, unable to say "no" to his first love, is drawn into a world of murder, betrayal, and secrets from which there is no escape.